Anthropogenic effects on greenhouse gas (CH4 and N2O) emissions in the Guadalete River Estuary (SW Spain) - Burgos, M.; Sierra, A.; Ortega, T.; Forja, J.M. (The Science of the total environment, 2015)
Coastal areas are subject to a great anthropogenic pressure because more than half of the world's population lives in its vicinity causing organic matter inputs, which intensifies greenhouse gas emissions into the atmosphere. Dissolved concentrations of CH4 and N2O have been measured seasonally during 2013 in the Guadalete River Estuary, which flows into the Cadiz Bay (southwestern Spanish coast). It has been intensely contaminated since 1970. Currently it receives wastewater effluents from cities and direct discharges from nearby agriculture crop. Eight sampling stations have been established along 18km of the estuary. CH4 and N2O were measured using a gas chromatograph connected to an equilibration system. Additional parameters such as organic matter, dissolved oxygen, nutrients and chlorophyll were determinate as well, in order to understand the relationship between physicochemical and biological processes. Gas concentrations increased from the River mouth toward the inner part, closer to the wastewater treatment plant discharge. Values varied widely within 21.8 and 3483.4nM for CH4 and between 9.7 and 147.6nM for N2O. Greenhouse gas seasonal variations were large influenced by the precipitation regime, masking the temperature influence. The Guadatete Estuary acted as a greenhouse gas source along the year, with mean fluxes of 495.7μmolm−2d−1 and 92.8μmolm−2d−1 for CH4 and N2O, respectively. •The estuary acts as a source of atmospheric methane and nitrous oxide.•Anthropogenic inputs affect the distribution of the greenhouse gases.•Dissolved gases presented an important longitudinal gradient.•Seasonal variations highly depended on the precipitation regimen.